Roux en Y gastric bypass hypoglycemia resolves with gastric feeding or reversal: Confirming a non-pancreatic etiology - Dawn Belt Davis; Jad Khoraki; Martynas Ziemelis; Sirinart Sirinvaravong; Jee Young Han; Guilherme M. Campos (Elsevier, 2018)
Objective: Postprandial hypoglycemia is an infrequent but disabling complication of Roux-en-Y gastric bypass (RYGB) surgery. Controversy still exists as to whether the postprandial hyperinsulinemia observed is due to inherent changes in pancreatic β-cell mass or function or to reversible alterations caused by RYGB anatomy. We aimed to determine if gastric feeding or reversal of RYGB would normalize postprandial glucose and hormone excursions in patients with symptomatic hypoglycemia. Methods: We completed a prospective study of six patients with severe symptomatic RYGB hypoglycemia who underwent RYGB reversal. An additional subject without hypoglycemia who underwent RYGB reversal was also studied prospectively. Mixed meal tolerance testing (MTT) was done orally (RYGB anatomy), via gastrostomy tube in the excluded stomach in the setting of RYGB, and several months after RYGB reversal. Results: All subjects reported symptomatic improvement of hypoglycemia after reversal of RYGB. Weight gain after reversal was moderate and variable. Postprandial glucose, insulin, and GLP-1 excursions were significantly diminished with gastric feeding and after reversal. Insulin secretion changed proportional to glucose levels and insulin clearance increased after reversal. Glucagon/insulin ratios were similar throughout study. We further compared the impact of modified sleeve gastrectomy reversal surgery to those with restoration of complete stomach and found no significant differences in weight regain or in postprandial glucose or hormone levels. Conclusions: Reversal of RYGB is an effective treatment option for severe postprandial hypoglycemia. The pathophysiology of this disorder is primarily due to RYGB anatomy resulting in altered glucose, gut, and pancreatic hormone levels and decreased insulin clearance, rather than inherent β-cell hyperplasia or hyperfunction. Keywords: Hypoglycemia, Insulin, Glucagon-like peptide 1, Roux en Y gastric bypass, Gastric bypass reversal, Bariatric surgery